Atypical Parkinson Syndrome Hiding a Meningioma. (December 2019) - Bund, Caroline; Ouvrard, Eric; Renaud, Mathilde; Tranchant, Christine; Namer, Izzie-Jacques
Abstract : Abstract: A 59-year-old man had developed within a few months walking disorders and rigidity of the left upper limb. 123 I-FP-CIT SPECT/CT was performed in response to the suspicion of atypical parkinsonian syndrome. It showed an anomaly in presynaptic dopaminergic transmission on the right striatum and a voluminous expansive process on CT. MRI revealed an atypical meningioma. The patient had surgery for tumor removal. Later 123 I-FP-CIT SPECT/CT showed normalization of presynaptic dopaminergic transmission on the right striatum.